Meningkatkan Kemampuan Matematika Anak dengan Word Wall di Taman Kanak-Kanak Telkom Jambi - Dewi Paluvi; Nurmalia; Huda (Mataram University, 2026)
This study aimed to improve the mathematical abilities of children aged 5–6 years through the use of the Wordwall learning media at Telkom Jambi Kindergarten. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, implemented in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 15 children in Group B aged 5–6 years. Data were collected through observation, documentation, and field notes, and were analyzed descriptively using percentages. The results showed that the use of Wordwall significantly improved the children's mathematical abilities. In the pre-action stage, only 20% of the children achieved the categories of Developing as Expected (BSH) and Developing Very Well (BSB). After the implementation of Wordwall in Cycle I, this percentage increased to 60%, and further improved to 93.3% in Cycle II. The improvement was reflected in the children's ability to recognize number symbols, match numbers with quantities of objects, arrange numbers in sequence, and perform simple arithmetic operations. These findings indicate that Wordwall creates a more interactive, engaging, and enjoyable learning environment, thereby enhancing children's participation and understanding of mathematics. Therefore, the Wordwall learning media is effective in improving the mathematical abilities of early childhood learners at Telkom Jambi Kindergarten.